Telepharmacy Knowledge, Perceptions, and Readiness among Future Malaysian Pharmacists Amid the COVID-19 Pandemic - Elnaem, Mohamed Hassan; Akkawi, Muhammad Eid; Al-Shami, Abdul Kareem; Elkalmi, Ramadan (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Telepharmacy is a relatively recent advancement in healthcare services that enables providing high-quality pharmacy services to rural and remote areas. It gained increased attention during the COVID19 pandemic. Objectives: To assess the knowledge, perceptions, and readiness towards telepharmacy services among senior pharmacy students in a Malaysian public pharmacy school. Materials and Methods: A cross-sectional study was conducted using a self-developed, pre-tested, and validated 35-item questionnaire among penultimate and final year students in a Malaysian public pharmacy school. Ethical approval was obtained before beginning the online data collection between September and December 2020. Descriptive and inferential data analyses were performed using SPSS version 22. A p-value ≤ of 0.05 was considered statistically significant. Results: The study received a total of 178 responses to the questionnaire. The response rates of the third and fourth years were 50.6% and 49.4%, respectively. Overall, 67% had high knowledge, and 68% showed high readiness level. Meanwhile, 61% of the responses had positive perceptions of telepharmacy services. A notably excellent knowledge was demonstrated in items related to the telepharmacy role during the pandemic (93.8%) and the technical competencies required for the service provider (96.1%). The beneficial role of telepharmacy to save patients’ resources was perceived positively with a 91% agreement level among study participants. The readiness items related to the lack of incentive and the excessive workload were associated with less agreement levels of 33.7% and 45.5%, respectively. Overall, participants’ knowledge of telepharmacy significantly impacted their expressed readiness to implement telepharmacy services in their future practice. Conclusion: Most study participants had adequate knowledge, positive perceptions and demonstrated readiness to implement telepharmacy services in their future pharmacy practice. The potential increase in workload and lack of incentive were the main concerns associated with the widespread adoption of telepharmacy practice models.
Keywords: Malaysia; Pharmacists; Readiness; Students; Telepharmacy